2010
DOI: 10.1039/b920131a
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of excited-state benzophenone ketyl radical in a room-temperature ionic liquid

Abstract: The photochemistry of benzophenone ketyl radical in the D 1 excited state, BPH(D 1 ), was studied by means of two-color dual-pulse laser flash photolysis (355 and 532

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…The k T-T values were experimentally obtained from the decay of 3 BP* observed at 610 nm to avoid contribution of BPH . The DA(t) curves were simulated by the Levenberg-Marquardt nonlinear least squares method with eqn (15). The fitting parameters are a 0 and k RP .…”
Section: Cage Lifetimes Of Ionic Liquidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The k T-T values were experimentally obtained from the decay of 3 BP* observed at 610 nm to avoid contribution of BPH . The DA(t) curves were simulated by the Levenberg-Marquardt nonlinear least squares method with eqn (15). The fitting parameters are a 0 and k RP .…”
Section: Cage Lifetimes Of Ionic Liquidsmentioning
confidence: 99%
“…48 In the report, the cage effects were found to increase with increasing macroviscosity from Emim BF 4 to PP13 TFSA. 47 The extensive studies on the nanoscale ordering structures of ILs have been reported, [8][9][10][11][12][13][14][15] however, the cage lifetime has not been reported until now. To the best of our knowledge, this is the first report on the cage lifetime of ILs.…”
Section: Cage Lifetimes Of Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, diffusion/mobility-controlled processes in ILs may proceed noticeably different compared to common organic solvents, ultimately leading to a change of the reaction pathways and the products formed. 13,14 Heterogeneities and nanostructuring of ILs have been of great interest for both experimental and theoretical studies. [5][6][7][8][9][10][11][12] It was found that charged cationic head groups and anions aggregate in polar nano-domains, whereas hydrophobic alkyl tails of cations aggregate in non-polar nanodomains.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] ILs also provide new environments for chemical reactions with applications in many fields, such as catalysis, synthesis, electron transport, polymerization, and formation of nanomaterials. Although a number of studies on the structure of ILs have been reported, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] the mechanistic details of chemical reactions in ILs remain relatively unstudied owing to ILs' tendency to form complex structures, such as nanoscale ordering structures. We have also studied the nanoscale ordering structures of ILs by the magnetic field effect probe (MFE probe).…”
Section: Introductionmentioning
confidence: 99%